Synthesize of ZnO Nanoparticle by Direct Reaction Between Zn and Water - Kazemzadeh*, Asghar; Alinejad, Babak; Mahmoodi, Korosh (Asian Journal of Chemistry, 2011)
A simple technique was invented based on combining top-down and bottom-up approaches for synthezing ZnO nano-particles using only Zn and water as starting materials. In this method, Zn powder was milled using a planetary ball. Then the milled powder was pured in warm water. Zn was hydrolyzed and ZnO powder was self-assembled in two different morphologies: hexagonal flakes with average size of ca. 200 nm and rod morphology with average height of ca. 100 nm and average diameter ca. 20 nm. The specific surface area of the powder was 18025 m2/g.